2010
DOI: 10.1007/s11356-010-0385-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paraoxon on spermatogenesis in Dugesia gonocephala from the Chilean Altiplano: proliferation and apoptosis

Abstract: Paraoxon inhibits DNA synthesis and induces apoptosis during spermatogenesis in adult planarians from a high-altitude, pollution-free environment. This could suggest its use as a biosensor or biomarker for contamination with agro pesticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Insecticide concentrations from 10 µM up to 1 mM were assayed and were in accordance with previous studies. Concentrations up to 800 µM paraoxon-ethyl were used for incubating planarians 25 , while concentrations ranging from 13 µM up to 57 µM were reported for diazinon, fenitrothion, parathion, chlorpyrifos and malathion 26 , 27 . The viability of D. japonica for concentrations up to 500 µM was also described and the authors showed that dichlorvos was 100 times more toxic than chlorpyrifos suggesting that toxicity is strongly dependent on the insecticide 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insecticide concentrations from 10 µM up to 1 mM were assayed and were in accordance with previous studies. Concentrations up to 800 µM paraoxon-ethyl were used for incubating planarians 25 , while concentrations ranging from 13 µM up to 57 µM were reported for diazinon, fenitrothion, parathion, chlorpyrifos and malathion 26 , 27 . The viability of D. japonica for concentrations up to 500 µM was also described and the authors showed that dichlorvos was 100 times more toxic than chlorpyrifos suggesting that toxicity is strongly dependent on the insecticide 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, planarians have emerged as an alternative animal model for toxicology and neurotoxicology 22 , 23 . Dugesia japonica 24 , D. gonocephala 25 , D. dorotocephala 26 , and D. tigrina 27 have been shown to be negatively affected by OP exposure. Cholinesterase activity was demonstrated in planarians and their sensitivity to OPs has been highlighted albeit lower than Homo sapiens AChE ( Hs- AChE) 24 .…”
Section: Introductionmentioning
confidence: 99%